En psykolingvistisk test til kvantificering af progression i indlæringen af italiensk som fremmedsprog: metoder og resultater - Kratschmer, Alexandra Regina; Bohn, Ocke-Schwen; Pierucci, Giulia; Hardman, Jocelyn B.; Gavagna, Diego (Ny forskning i grammatik, 2016)
This article describes a psycholinguistic protocol designed to elicit individual differences in performance regarding phonological (sound discrimination) and lexical (vocabulary memorization) aspects of learning Italian as a foreign language. An experiment built on that protocol revealed a wide range among participants regarding the number of novel vocabulary items memorized as well as a minor spread regarding the discrimination of a novel Italian consonant contrast. No correlation could be revealed between learning success in vocabulary acquisition and phonological discrimination. We conclude that the two types of tasks can be used as instruments for quantifying aspects of learning Italian as a foreign language.